Evaluación de la calidad de vida de pacientes con insuficiencia renal crónica terminal que reciben diálisis peritoneal ambulatoria continua. Hospital II Essalud Tarapoto. Junio - Noviembre 2012 - Flores Flores, Rosita Dina (2012)
This research entitled: Evaluation of the Quality of Life of Patients with Chronic Renal Failure That Receive CAPD. Hospital II Essalud Tarapoto. June - November 2012. He was raised as a mere descriptive research, where the use of a single box design, aiming to determine the quality of life of patients with ESRD who perform CAPD Hospital II EsSalud Tarapoto . The population was represented by 31 patients who met the inclusion criteria. For data collection, the method of interview, applying the generic Quality of Life SF-36 to determine the quality of life of patients with ESRD who perform CAPD as components physical health: physical functioning, role physical, bodily pain and general health and mental health components: vitality, social function, role emotional and mental health of patients. The data were systematized using SPSS version 17.0. The findings were: 35.5% rated their health in general, better now than a year ago, 58.1% reported health condition that limits physical activities of daily life, the 71.0% reported role Poor physical, occurring as a result performance at work and other daily activities less than desired; 61.3% referred for pain intensity good, which has no effect on their normal work and activities of the patient's home, the 54.8% reported negative state of general health, 71.0% reported feeling of energy and vitality of good versus fatigue and discouragement, 61.3% reported that the degree of physical or emotional problems stemming from the lack your health do not interfere in their usual social life, 51.6% reported that emotional problems do not affect their work and other daily activities and 51.6% rated their overall mental health as good.